The Effectiveness of BISAP Score for the Diagnosis of Severe Acute Pancreatitis - Azeen Razzaq, Muhammad Haroon Abdullah, Zulquernain Ahmed Zoak, Paras Yousuf, Aan-E-Arshad Sh, Hajra Tariq, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The clinical profile of severity of acute pancreatitis ranges from modest pancreatic inflammation to an unusually fatal acute necrotizing pancreatitis rightly known as severe acute pancreatitis (SAP). For the evaluation of clinical spectrum of pancreatitis, a more accurate models that is also cost-effective is required. Here, we sought to evaluate the contribution BISAP scoring systems to the diagnosis of severe of acute pancreatitis by comparing it with CT severity index. Settings and duration: This observational study was carried out at medicine department, Jinnah hospital, Lahore from 16th July 2022 to 15th January 2023. Sampling: Patients diagnosed with acute pancreatitis were registered. Acute pancreatitis was labelled based triad of classic epigastric pain, blood markers and imaging tool. BISAP score ≥3 was meant SAP and CT severity index for SAP included findings like necrosis and collection. Diagnostic accuracy was determined. Results: The patient's age ranged from 20 to 60 years with mean age of 36.41 + 9.362 years. The ratio of male to female participants was 2.3 to 1. For the diagnosis of SAP, the BISAP score's sensitivity, specificity, positive predictive value, negative predictive value, and accuracy were each 95.8%, 55.2%, 85.2%, 83.3%, and 84.8%, respectively. Conclusion: Simple clinical tools like BISAP score could be helpful in diagnosing severe acute pancreatitis, precluding the need for expensive and technically complex imaging modalities. Keywords: Severe acute pancreatitis (SAP), BISAP Score, Diagnostic accuracy